Harnessing Dynamic Capabilities: Analyzing the Income Disruption in Agribusiness with the Cox PH Model - Srishti Saxena; Manju Singh; Gyanendra Singh Sisodia (SAGE Open)
The study analyzes the impact of financial incentives, production inputs, technology adoption, policy infrastructure, and labor dynamics on the likelihood of Income Disruption (ID) events in agribusinesses. The research identifies key financial metrics contributing to ID risks using the Cox Proportional Hazards (PH) Model and time-to-failure data from 1- to 2-year prior models. Agribusinesses are classified into Super, A, B, C, and D categories based on their agricultural wholesale produce market registration. This study focuses on the IIIA Agro Climatic Zone of Rajasthan, a semi-arid region consisting of districts such as Jaipur, Ajmer, Tonk, and Dausa. Characterized by erratic rainfall, poor water retention, and extreme temperatures, agribusinesses in this zone encounters heightened ID risks due to environmental and infrastructural challenges. The findings show that excessive spending relative to income, low profit margins, and poor asset returns significantly increase ID risk in the 1-year model. In the 2-year model, factors such as gross loan charge-offs relative to income also elevate ID risk. However, when appropriately leveraged, financial incentives and subsidies reduce the likelihood of income disruptions. The study emphasizes the importance of financial strategies, including subsidies and technology adoption, to mitigate risks in agribusinesses. From a policy perspective, the results underscore the need for long-term investments in climate-smart agriculture. Policymakers should focus on improving access to credit, supporting digital transformation, and fostering resilience through sustainable agricultural practices. These strategies will enable agribusinesses to endure the challenges of climate variability and market volatility, contributing to their overall financial sustainability. JEL Codes: C41, C44, C55.